2014
DOI: 10.1016/j.envint.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Source attribution of personal exposure to airborne polycyclic aromatic hydrocarbon mixture using concurrent personal, indoor, and outdoor measurements

Abstract: Objectives Relative importance of multiple indoor and outdoor venues on personal exposure concentrations to pro-carcinogenic polycyclic aromatic hydrocarbons (c-PAHs) remains poorly understood. This is particularly challenging because many c-PAHs share sources and occur as a complex mixture. Accurate and precise apportionment of personal exposure according to exposure venues could aid in understanding of human health effects due to given source. Here, we partitioned indoor and personal exposure concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
2
24
1
Order By: Relevance
“…In recent years, the passive air samplers (PAS) based on sorbent disks of polyurethane foam housed in stainless steel protective chambers are widely used for the sampling of atmospheric persistent organic pollutants. These devices do not require any electric pump and can be installed in many sites, and provide high retention capacity for many organic compounds (Harner et al, 2004;Choi and Spengler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the passive air samplers (PAS) based on sorbent disks of polyurethane foam housed in stainless steel protective chambers are widely used for the sampling of atmospheric persistent organic pollutants. These devices do not require any electric pump and can be installed in many sites, and provide high retention capacity for many organic compounds (Harner et al, 2004;Choi and Spengler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier analyses showed that PAH of outdoor origin are the predominant contributor to personal exposure (Choi et al, 2008a; Choi and Spengler, 2014). Furthermore, proxy variables, such as home heating demand in degrees and wind speed, significantly predicted the ambient PAH concentrations (shown in Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…As described elsewhere (Choi et al, 2008a; Choi et al, 2008b; Choi and Spengler, 2014), the home indoor and the home outdoor PAH monitoring were conducted concurrently with the personal exposure monitoring. For indoor monitoring, the backpack was placed in a room where the woman spent most of her time at home (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations